Generative AI for Students: Inovasi Pembelajaran Digital untuk Peningkatan Pemahaman dan Manfaatnya bagi Mahasiswa - Okky Putra Barus; Yugopuspito, Pujianto; Pangaribuan, Jefri Junifer; Romindo, Romindo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The rapid development of artificial intelligence (AI) technology demands increased AI literacy among students. Generative AI, as a growing branch of AI, offers great potential to transform the learning process. Unfortunately, the level of AI literacy in Indonesia is still low. The study